Using the Debiased Brier Skill Score to Evaluate S2S Tropical Cyclone Forecasting - Yuanben Li; Xiaochun Wang; Bingke Zhao; Ming Ying; Yimin Liu; Frederic Vitart (Journal of Marine Science and Engineering, 2025)
To evaluate tropical cyclone forecasting on synoptic timescale, tracking and intensity are used. On subseasonal to seasonal (S2S) timescale, what aspects of tropical cyclones should be predicted and how to evaluate forecasting skills still remain open questions. Following our previous work, which proposed using daily tropical cyclone probability (DTCP) as a measure of tropical cyclone activity and the debiased Brier skill score (DBSS) to evaluate tropical cyclone forecasting on S2S timescale, the present research investigates the influence of several factors that may influence the use of DTCP and the DBSS framework. These factors are the forecast time window, tropical cyclone influence radius, evaluation region, forecast sample, and how the Brier score for the reference climate forecast is computed. The influence of these factors is discussed based on the output of the S2S prediction project database and comparison of the DBSS when the above factors are changed individually. Changes in the forecast time window, evaluation region, and tropical cyclone influence radius can change the DTCP. The larger the tropical cyclone influence radius and the longer the forecast time window, the larger the DTCP will be. However, the spatially averaged DBSS changes very little. Using estimated Brier score for reference climate forecast can cause variation due to limited forecast samples. It is recommended to use the theoretical value of the Brier score for reference climate forecasting, instead of its estimation.